Pengaruh Bagian Kayu dan Ketebalan Stiker pada Pengeringan Alami terhadap Sifat Fisika Kayu Gerunggang (Cratoxylon arborescens Bl.) - Gimson Luhan; M Damiri; Herwyn Joni; Yanciluk; Ahmad Mujaffar (Jurnal Hutan Tropika, 2019)
The existence of the wood needs to be considered so that the use of wood for a particular use needs to pay attention to the quality of wood, both for wood for building materials, furniture, panels, crafts and so on. The weakness of wood compared to substitutes such as metal and concrete is its hygroscopic nature. The aim of this study was to determinethe effect of wood parts treatment on axial direction and sticker thickness on natural drying time on changes in the physical properties of gerunggang wood (Cratoxylon arborescens Bl.). While the expected benefits are as information material for the wood processing industry and wood users to be able to dry the wood properly. The research was conducted at the Forest Products Technology Laboratory for 3 months. Cutting is done by dividing the length of the stem into 3 (three) equal parts in the axial position, namely the base (a1), middle (a2) and end (a3), each cut length ± 2 m for the board (example drying test) ) with ± 2 cm thick and ± 15 cm long for example test of moisture content, specific gravity and shrinkage. The results showed that the average value of fresh water content, saturated point moisture content, and air dry water content had a tendency to decrease in value from the base to the end of the stem. The natural dryingtime has an average tendency to dry more quickly from the base to the end of the stem, with drying times ranging from 28-40 days or an average of 33 days. The end of the wood with a thickness of 3,5 cm sticker dries faster (25 days) with a defect 1 broken edge. Parts of wood with a sticker thickness of 3,5 cm dries faster than the thickness of the stickers 2,5 cm and 1,5 cm. The results of measurements of (BJ) density of gerunggang wood averaged 0,55 including the medium group (BJ 0,4-0,6). Specific gravity has a tendency to increase in value from the base to the end of the rod with an uneven pattern including type 3. The tangential and radial direction shrinkage ratio of 1,88 is included in the medium classification, then gerunggang wood can be used for boards and lightweight construction under the roof, crates, furniture, plywood andconcrete molds. It is recommended to conduct further research on the possibility of using gerunggang wood for artificial boards.Keywords: drying, wood parts, physical properties, gerunggang.